The effectiveness of guided inquiry learning tools in increasing students' activities and creative thinking skills. Issue 1 (February 2021) - Widia,; Sarnita, F; Irawan, A; Syafrudin,; Armansyah,; Nurdiana,; Hunaepi,; Sapnowandi,; Prayogi, S; Asy'ari, M
Abstract: This study aimed to describe the effectiveness of guided inquiry learning tools in increasing students' creative thinking activities and skills. Student activities include: paying attention, formulating problems, hypothesizing, conducting experiments, recording observations, discussing, communicating results, and concluding, while creative thinking skills components namely: fluency, flexibility, originality, and elaboration were also identified in this study. The study used a one-group pre-test post-test design which was implemented on 22 students. Research data were collected using activity observation sheets and creative thinking skills test instruments. The results showed that the activity and creative thinking skills of students increased after learning, so it can be concluded that guided inquiry learning tools were effective in increasing students' activities and creative thinking skills.